Computational modeling of aberrant electrical activity following remuscularization with intramyocardially injected pluripotent stem cell-derived cardiomyocytes - Yu, Joseph K.; Liang, Jialiu A.; Weinberg, Seth H.; Trayanova, Natalia A. (Journal of molecular and cellular cardiology, 2022)
Acute engraftment arrhythmias (EAs) remain a serious complication of remuscularization therapy. Preliminary evidence suggests that a focal source underlies these EAs stemming from the automaticity of immature pluripotent stem cell-derived cardiomyocytes (PSC-CMs) in nascent myocardial grafts. How these EAs arise though during early engraftment remains unclear. In a series of in silico experiments, we probed the origin of EAs—exploring aspects of altered impulse formation and altered impulse propagation within nascent PSC-CM grafts and at the host-graft interface. To account for poor gap junctional coupling during early PSC-CM engraftment, the voltage dependence of gap junctions and the possibility of ephaptic coupling were incorporated. Inspired by cardiac development, we also studied the contributions of another feature of immature PSC-CMs, circumferential sodium channel (NaCh) distribution in PSC-CMs. Ectopic propagations emerged from nascent grafts of immature PSC-CMs at a rate of <96 bpm. Source-sink effects dictated this rate and contributed to intermittent capture between host and graft. Moreover, ectopic beats emerged from dynamically changing sites along the host-graft interface. The latter arose in part because circumferential NaCh distribution in PSC-CMs contributed to preferential conduction slowing and block of electrical impulses from host to graft myocardium. We conclude that additional mechanisms, in addition to focal ones, contribute to EAs and recognize that their relative contributions are dynamic across the engraftment process. [Display omitted] •Acute engraftment arrhythmias remain a serious complication of remuscularization.•Spontaneous beats in graft myocardium intermittently propagated into the host.•Immaturity of graft myocytes contributed to propensity for entrance block.•Site of graft-induced ectopic propagations could change from beat-to-beat.•A reentrant mechanism is likely to contribute to engraftment arrhythmias.